PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN METODE GUIDED WRITING PADA PESERTA DIDIK KELAS V SDN 10 BANDAR BUAT KOTA PADANG - Aulida, Rini; Yenti, Yesni; M. Habibi; Inggria Kharisma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low descriptive text writing skills of students. This was caused by several factors: students still had difficulties expressing their ideas and thoughts in written form or essays; students were not yet able to write descriptive texts according to their structure; students were not yet able to describe the suitability of the essay content with the determined topic in writing texts; students paid less attention to proper and correct grammar; students had difficulties in using the Indonesian Spelling System EBI correctly, especially in the use of capital letters and punctuation marks; and students lacked appropriate word choice in writing descriptive texts. The purpose of this study was to describe the improvement of students' descriptive text writing skills through the Guided Writing learning method in Grade Five of SDN Bandar Buat Padang City. This study was a Classroom Action Research using qualitative and quantitative approaches. The subjects of this research were the teacher and students of Grade Five at SDN Bandar Buat Padang City. The results of the study showed improvements in suitability of essay content, organization, word choice, language use, mechanics. After the implementation of the guided writing method, students' descriptive text writing skills increased from cycle I to Cycle II. Thus it can be concluded that the Guided Writing learning method can improve the descriptive text writing skills of Grade Five students in elementary school.